Voltage-Gated Calcium Channels - Zamponi, Gerald Werner (Molecular Biology Intelligence Unit, 2005)
oltage-gated calcium channels are essential mediators of a range of physiological functions, including the communication between nerve Vcells, the regulation of heart beat, muscle contraction, and secretion of hormones such as insulin. Consequently, these channels are critical phar macological targets in the treatment of a variety of disorders, such as epi lepsy, hypertension, and pain. Voltage-gated calcium channels have there fore been subject to intense study by numerous investigators over the past few decades, and an immense body of work has accumulated. In this book, we provide the first comprehensive overview of our current state of knowl edge concerning this exciting field of research. Leading off with a general review of calcium signaling and techniques to measure calcium channel ac tivity, the book delves into a provocative overview of the history of the cal cium channel field, contributed by one of the key pioneers in the field. Dr. Richard Tsien. This is followed by an in depth review of the biochemical and molecular biological characterization of calcium channel genes by Drs. Catterall and Snutch whose research has resulted in major advances in the calcium channel field. A number of chapters are dedicated towards various aspects of calcium channel structure and function, including channel gat ing, permeation, modulation and interactions with members of the exo- totic machinery-contributed by both established leaders and rising stars in the field.